REVISITING THE TAXONOMY OF TARENNA FLAVA ALSTON (RUBIACEAE: IXOROIDEAE) - Nair, Maya Sukumaran; Konickal Mambetta Prabhukumar; Sunilkumar Trivikraman Pillai; Tarun Chhabra (Phytotaxa, 2022)
The present paper discusses the identity and distribution of Tarenna flava Alston (Rubiaceae: Ixoroideae) in India. Detailed description with colour photographs are provided along with morphological comparison of the allied species Tarenna asiatica (L.) Kuntze ex K. Schum. Here we also designated the lectotypes for the names Tarenna flava and Stylocoryna webera A. Rich var. montana Thwaites.